Effective and diastereoselective preparation of dispiro[cyclopent-3′-ene]bisoxindoles via novel [3 + 2] annulation of isoindigos and MBH carbonates. Issue 8 (1st February 2018) - Ren, Hong-Xia; Peng, Lin; Song, Xiang-Jia; Liao, Li-Guo; Zou, Ying; Tian, Fang; Wang, Li-Xin
Abstract : Efficient, one-step preparation of highly steric dispiro[cyclopent-3′-ene]bisoxindoles with two all-carbon quaternary spirocenters and three adjacent cycles in excellent yields and diastereoselectivities under mild conditions. Abstract : A novel and diastereoselective [3 + 2] annulation of isoindigos and Morita–Baylis–Hillman carbonates has been developed for the highly efficient and one-step preparation of highly steric dispiro[cyclopent-3′-ene]bisoxindoles with two all-carbon quaternary spirocenters and three adjacent cycles in excellent yields (up to >99%) and diastereoselectivities (up to >20 : 1) under mild conditions within a few minutes. A series of dispiro[cyclopent-3′-ene]bisoxindoles were obtained and scale-up experiment was conducted with excellent results demonstrating the potential applications of this protocol.